2006
DOI: 10.1136/bmj.38748.697465.55
|View full text |Cite
|
Sign up to set email alerts
|

Factors predisposing women to chronic pelvic pain: systematic review

Abstract: Objective To evaluate factors predisposing women to chronic and recurrent pelvic pain. Design, data sources, and methods Systematic review of relevant studies without language restrictions identified through Medline, Embase, PsycINFO, Cochrane Library. SCISEARCH, conference papers, and bibliographies of retrieved primary and review articles. Two reviewers independently extracted data on study characteristics, quality, and results. Exposure to risk factors was compared between women with and without pelvic pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
338
10
47

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(407 citation statements)
references
References 48 publications
12
338
10
47
Order By: Relevance
“…Unsuitable, demonstrably ineffective or harmful methods: magnetic therapy, osteopathy, manual therapy, avoidance of coffee, cola and/or alcohol, homoeopathy, and relaxation therapy [80][81][82][83][84][85]. Possibly useful methods: traditional Chinese herbal medicine, acupuncture and acupressure, moxibustion, omega-3 fatty acids, vitamin B1, vitamin E, magnesium, exercise, yoga, chaste tree, yarrow, toki-shakuyaku-san -Kampo medicine from Japan, cinnamon [81,[86][87][88][89][90][91][92][93][94][95].…”
Section: Apitherapeutic Recommendations For the Treatment Of Primary mentioning
confidence: 99%
“…Unsuitable, demonstrably ineffective or harmful methods: magnetic therapy, osteopathy, manual therapy, avoidance of coffee, cola and/or alcohol, homoeopathy, and relaxation therapy [80][81][82][83][84][85]. Possibly useful methods: traditional Chinese herbal medicine, acupuncture and acupressure, moxibustion, omega-3 fatty acids, vitamin B1, vitamin E, magnesium, exercise, yoga, chaste tree, yarrow, toki-shakuyaku-san -Kampo medicine from Japan, cinnamon [81,[86][87][88][89][90][91][92][93][94][95].…”
Section: Apitherapeutic Recommendations For the Treatment Of Primary mentioning
confidence: 99%
“…Because the primary interference of vulvodynia is with sexual activity, the woman and partner each confront the problem independently, but they also face it together as an interdependent dyadic unit (Latthe, Mignini, gray, Hills, & Khan, 2006). It is therefore important to obtain separate reports from both partners, in order to isolate the effects of male partner responses perceived by the woman from those perceived by the male partner himself.…”
mentioning
confidence: 99%
“…However, a recent systematic review located only one published randomised controlled trial and this was published two decades ago. 12 In this trial those randomised to exercise reported significantly lower dysmenorrhoea symptomatology than non-exercising controls, but the sample size was very small (n = 36) with only 26/36 participants completing follow-up. Several additional non-randomised intervention studies were located by the review 13 but these were also of very poor methodological quality, the most recent of which was published over 40 years ago.…”
Section: Primary Dysmenorrhoeamentioning
confidence: 99%